“PSEUDO-SARMATIAN” MOLLUSC ASSEMBLAGES FROM THE EARLY MESSINIAN OOLITE SHOALS OF SICILY (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
We present a revision of the Late Miocene mollusc assemblages from Faro Santa Croce (FSC) in SE Sicily. The FSC-section exposes lower Messinian coastal marine limestones of the Monte Carrubba Formation. Whilst the lowermost part is characterised by in situ occurrences of pen shells ( Atrina fragilis ), the larger part comprises cross-bedded oolites alternating with rock-forming cardiid-venerid coquinas. Due to their superficial similarity with Paratethyan Sarmatian assemblages, the taxa were partly identified as Sarmatian species in previous literature, resulting in a surprising diachronous occurrence of otherwise endemic Paratethyan species in the early Messinian Mediterranean Sea. Therefore, in respect to the ongoing discussion on Mediterranean-Paratethyan faunal exchange during Messinian times, a critical taxonomic re-evaluation of the mollusc assemblage appeared crucial for palaeo(bio)geographic interpretations. The revision of the fauna proofs the absence of any relations with the Sarmatian faunas of the Paratethys Sea; about 20% of the species from the Messinian part of the section are restricted to the Late Miocene and are typical Mediterranean elements. Similarly, no hint to lowered salinities can be deduced from the normal marine stenohaline assemblages. Their co-occurrence in oolitic shoals may rather point to somewhat hypersaline and alkaline settings in a strongly agitated environment.
Keywords: Messinian; mollusca; oolites; Sicily; Paratethys Sea; biogeography